The Effect of Financial Literacy on the Financial Management of MSMEs in Jatinangor District, Sumedang Regency - Wirawan Widjanarko; Wastam Wahyu Hidayat; Ery Teguh Prasetyo; Idel Eprianto; Yulianah (Institute of Computer Science (IOCS), 2022)
The ability to understand and manage one's personal finances is what we mean when we talk about financial literacy. Understanding money matters is crucial when running a small or medium business (SME). The purpose of this research is to investigate and analyze the way that financial literacy affects the way that MSMEs in Jatinagor, a subdistrict of Sumedang Province, handle their money. There were 72 participants in this study, and the researchers used a descriptive quantitative methodology. Simple linear regression analysis and descriptive statistics are the methods employed. Based on the available data, financial literacy has a minimal effect on financial management (31.7% to be exact), while other factors (68.3%) are more significant. Small and medium-sized enterprises (SMEs) in the Jatinangor District have a low level of financial literacy. To better assist MSMEs with financial management, it is necessary to increase financial knowledge. Several factors, such as education level, exposure to financial information, and age of MSME actors, contribute to the low financial literacy of MSMEs in this study